POPULATION VARIATION IN THE ONCOCYCLUS IRISESALONG A GEOGRAPHICAL GRADIENT IN ISRAEL - SAPIR, Y.; SHMlIDA, A.; RITTE, U (Annali di Botanica, 2000)
TIle section Oncncyclus of lhe genus Iris L. comprises eight species in Israel, which are among the most beautiful and important planL'i for conservation. Three of the dark-coloured species (f. haney.f. atrofusca and f. petrana) are distributed along the North-South climatological gradient in Ismel. Although many taxonomists have dealt with !.his stXlion in the last century, no quantitative research has been done. Many transitional fonns between species or populations are known from lite field. The purpose ofthc current reaearch was to test quantitatively, by using inter and intra pulation variation. the relationship among those species. and to examine whether morphological trait changed along the ecogeographical North-South gradient. Morphological traits were measured in eleven populations along this gradient. Intrapopulation variation is signiticantly higher than variation between each nearest population for most characters. Morphological distance was calculated using the Pearson distance coefficient. and is significantly correlated with geographical distance. Regression of all traits against latitude revealed that diagnostic characters, especially flower sizc, stcm height and leaf characters, change along the aridity gradient.